An assessment of an adapted version of the arthritis impact measurement scales short-form questionnaire to determine health-related quality of life in Vietnamese patients with arthritis - Trung Quang Vo (2019)
© 2018, Journal of Clinical and Diagnostic Research. All rights reserved. Introduction: Arthritis significantly decreases the physical and psychological health of patients and is a leading cause of disability. In recent years, the importance of measuring Health-Related Quality of Life (HRQOL) is increasingly recognised by clinicians and policy-makers in informing patient management and policy decisions, especially in the management of patients with chronic diseases. Aim: The primary objective was to evaluate the psychometric properties of a culturally adapted (Vietnamese) version of the internationally recognised Arthritis Impact Measurement Scales short-form (AIMS2-SF) questionnaire for use in Vietnamese-speaking patients with Osteoarthritis (OA) and Rheumatoid Arthritis (RA) (Vie-AIMS2-SF). The secondary objectives were to demonstrate the HRQOL of patients with arthritis and identify socio-demographic factors that impacted on HRQOL. Materials and Methods: This observational, cross-sectional study was conducted on a convenience sample of Vietnamese patients (n=333, 207 women), presenting at a public, specialist orthopaedic hospital in Ho Chi Minh City, southern Vietnam, from January to March 2018. The patients were directly interviewed with the Vie-AIMS2-SF. The reliability and validity of the questionnaire were evaluated by using Cronbach's alpha coefficient (α) and Exploratory Factor Analysis (EFA) respectively. Results: The Vie-AIMS2-SF met the criteria of reliability and validity. Twenty-six items were identified and categorised as five key components: physical (upper and lower limb function), affect, symptom, role and social interaction. Cronbach's alpha coefficient for the Vie-AIMS2-SF Questionnaire ranged from 0.52 to 0.88 indicates a good internal consistency. Regarding HRQOL score, the mean score ranged from 2.3±1.7 for the physical component to 5.0±2.3 for the symptom one. After applying the multivariable linear regression, monthly income and income satisfaction were found to be statistically significant with majority of components (p<0.050). Conclusion: The Vie-AIMS2-SF questionnaire was found to be a valid and reliable instrument to use as assessing HRQOL of Vietnamese patients with arthritis. HRQOL was observed to be “moderate” and several socio-demographic factors should be taken into account in order to improve the HRQOL in this population.